Bringing order to a chaotic restaurant - Venkataraman, Ray R.; Pinto, Jeffrey K. (Los Angeles, CA : SAGE Publications, Inc., 2017)
This case describes the consequences of poor material requirements planning for Amy Peters, the co-owner of Vistas, a restaurant in Stamford, Connecticut. Customers stopped patronizing Vista because they were dissatisfied with the unavailability of advertised entr?es as the kitchen had run out of stock of many food ingredients early in the evening. The case illustrates the importance of materials management in matching supply with demand to maintain a high level of customer satisfaction. It relates material management with the functions of a master schedule that disaggregates a sales and operations plan into detailed material and resource plans of end items needed to meet demand.
Originally published in Venkataraman, R. R., & Pinto, J. K. (2017). Bringing order to a chaotic restaurant. In Operations management: Managing global supply chains (p. 682). Thousand Oaks, CA: SAGE Publications. ISBN: 9781506302935.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Vistas (Restaurant : Stamford, Conn.); Restaurant management; Material requirements planning